(untitled) (LEARNing Landscapes, 2021)
Pedagogy can be understood as methods and practices of teaching, and/or a way of being with children. In this paper, I use critical exposition and narrative to reflect on Max van Manen’s (2012) theory of pedagogy as a relationship between adults and children. My writing is organized into alternating sections of exposition (theory) and narrative (practice) to illustrate the interplay between thinking and doing that typifies pedagogical relationships, and to demonstrate how pedagogy unfolds in the unpredictable, unexpected, unprecedented, and unique actions each of us perform in the relational events of our being with children.